E-cigarette puffing patterns associated with high and low nicotine e-liquid strength: effects on toxicant and carcinogen exposure. (December 2016) - Cox, Sharon; Kośmider, Leon; McRobbie, Hayden; Goniewicz, Maciej; Kimber, Catherine; Doig, Mira; Dawkins, Lynne
Abstract Background Contrary to intuition, use of lower strength nicotine e-liquids might not offer reduced health risk if compensatory puffing behaviour occurs. Compensatory puffing (e.g. more frequent, longer puffs) or user behaviour (increasing the wattage) can lead to higher temperatures at which glycerine and propylene glycol (solvents used in e-liquids) undergo decomposition to carbonyl compounds, including the carcinogens formaldehyde and acetaldehyde. This study aims to document puffing patterns and user behaviour associated with using high and low strength nicotine e-liquid and associated toxicant/carcinogen exposure in experienced e-cigarette users (known as vapers herein). Methods/design A counterbalanced repeated measures design.Participants: Non-tobacco smoking vapers; have used an e-cigarette for ≥3 months; currently using nicotine strength e-liquid ≥12mg/mL and a second or third generation device.Intervention: This study will measure puffing patterns in vapers whilst they use high and low strength nicotine e-liquid under fixed and user-defined settings, each for a week. The 4 counterbalanced conditions are: i) low strength (6mg/mL), fixed settings; ii) low strength user-defined settings; iii) high strength (18mg/mL) fixed settings; iv) high strength user-defined settings. Biomarkers of exposure to toxicants and carcinogens will be measured in urine. In the second phase of this study, toxicant yields will be measured in aerosol generated using a smoking machine operated to replicate the puffing behaviours of each participant.Primary outcomes: i) Puffing patterns (mean puff number, puff duration, inter-puff interval and mL of liquid consumed) and user behaviour (changes to device settings: voltage and air-flow) associated with using high and low strength nicotine e-liquid. ii) Toxicant/carcinogen exposure associated with the puffing patterns/device settings used by our participants.Secondary outcomes: i) Subjective effects. ii) comparisons with toxicant exposure from tobacco smoke (using documented evidence) and with recommended safety limits.Sample size: Twenty participants. Discussion The findings will have important implications for public health messaging regarding the relative risks and subjective effects associated with using high and low strength nicotine e-liquid, and for policy makers regarding regulations on nicotine concentrations in e-liquids.